Effect of Organization Culture on organization performance on Public Universities in Kenya - Gulali Donald Indiya; Johnmark Obura; J.K Mise (European Scientific Journal, ESJ, 2018)
Organizational culture is the adhesive holding companies together in a country and is characterized by stability processes, collectivity and predictability, and is a source of recreation, of new opportunities as well as of conflicts and of dynamics. Recent studies on organization culture have anchored organization culture on individualism, uncertainty avoidance power distance, masculinity and long term orientation, employee longevity, adhocracy culture and clan culture. This contradictions reveal that it remains unknown of organization culture based on individual values, assumptions, values and artifacts influence organization performance. This study seeked to establish the effects of organization culture on organization performance in public universities in Kenya. Guided by Contingency Theory of organization structure, a correlation research design and a population of 215 management personal were used from 11 public universities in Kenya certified by Kenya Bureau of Standards. The study adopted a census survey with response at 94.4 %. Primary data was collected using questionnaires. Using Pearson Product Moment Correlation the study indicates that there was a strong positive significant correlation between organizational culture and organizational performance (r=.804, p<.05). Regression analyses revealed that organizational values had the strongest unique contribution to the organizational performance (β=.394, p=.000), followed by organizational artifacts (β=.347, p=.000) and finally individual believes (β=.155, p=.001). The overall form of organizational culture had a unique significant contribution on organizational performance (β=.804, p=.000), and accounted for 64.6% variance in organizational performance. The study recommends that universities should work on ensuring that there are positive believes that can enhance organizational performance through improving and maintaining quality management systems basing on the existing culture.